Simulation Investigation of Rolling Sphere Method as Lightning Protection System for Buildings Using AutoCAD - 3D Lightning Software - Yanuar Zulardiansyah, Arief; Jefferson, Sait; Aulia, Aulia; Naemah, Mubarakah; Yulianta, Siregar; Hendri, Masdi (2024)
A lightning protection system (LPS) is one of the protection systems that has been used to protect structures from fire or mechanical destruction. LPS also prevents the person in the building from being injured or killed during the lightning strikes the ground. The failure to install or design the LPS will increase the hazard to the building, electrical and electronic devices, and humans. Incorrect implementation of LPS can cause the chance of lightning strikes on unprotected parts of the building to increase. The structure that contains toxic, flammable, or explosive products would likely cause the hazard to increase beyond the incident area. To solve this issue, a simulation of the rolling sphere method (RSM) has been performed for the selected buildings of UNIMAS, which are the Faculty of Engineering (FENG) and Chancellery buildings. In this work, two elements will be studied namely lightning protection zone and the area of protection for the building. To study the lightning protection area, the simulation will be conducted by using the 3D lightning application on AutoCAD. The length of the lightning arrester has been manipulated to observe the changes lightning protection zone for every lightning protection level. Furthermore, an improvement on the LPS design for both buildings was been completed based on the simulation result of the original building design. For the FENG building, the best design was to use 2.0 m of lightning arrester rod while the Chancellery building used 1.0 m of lightning arrester rod since the protection zone of 1.0 m was nearly the same as the 2.0 m one.